Pengaruh Kualitas Layanan Dan Harga Terhadap Loyalitas Konsumen Melalui Kepuasan Konsumen Pada Layanan Ride Hailing Goride - Kristiana, Arisqa Adira; Rubiyanti, R. Nurafni (eProceedings of Management, 2024)
Congestion will continue to occur with the increasing number of motorized vehicles, but with the development oftechnology, various innovations to reduce congestion have emerged, one of which is ride hailing. However, it cannotbe denied that competition between ride hailing companies is getting tighter so that companies must think about howto maintain and increase customer satisfaction and loyalty, one of which is by looking at service quality and pricefactors. This study set out to ascertain the impact of pricing and service quality on consumer fulfillment and loyalty,with a focus on Bandung City students who utilize GoRide ride-hailing services. Quantitative techniques withdescriptive causality are employed in this study. 135 students in Bandung City were used as the sample population,and the nonprobability sampling technique using purposive sampling types was used to conduct the sampling. PartialLeast Square (PLS) - Structural Equation Modeling (SEM) with SmartPLS 3.2.9 application being the data analysismethod employed. The study's findings indicate that customer satisfaction is significantly impacted by the quality ofthe services provided. The impact of cost on customer satisfaction is noteworthy. Customer loyalty is not significantlyimpacted by service quality. Customer loyalty is significantly impacted by customer satisfaction. Through clienthappiness, service quality has a major impact on customer loyalty. Through client happiness, price has a big impacton consumer loyalty.Keywords-service quality, price, consumer loyalty, consumer satisfaction